AN EPIDEMIC OF GASTROENTERITIS IN KARACHI - Mohammad Zohair Hussain ALi Lilani; Rabbia Tazeem; Namra Sharief (Journal of University Medical & Dental College, 2017)
ABSTRACT: In Pakistan there have been many epidemics of Gastroenteritis reported in the last few years. The main reason for these epidemics are poor sanitary conditions in low economical area of Pakistan and unawareness among the people of Pakistan about the use of clean water. In this letter, I tried to highlight those factors of these epidemics which were involved in the recent epidemic of Gastroenteritis in Karachi. Also, I tried to suggest different measures which can be useful to prevent such epidemics in the region.